2006
DOI: 10.1016/j.fishres.2005.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Pelagic longline gear depth and shoaling

Abstract: Temperature-depth recorders (TDRs) were attached to pelagic longline gear in the Hawaii-based commercial fishery to obtain actual fishing depths and to test the accuracy of catenary algorithms for predicting fishing depths. Swordfish gear was set shallow by typically deploying four hooks between successive floats. The observed depth of the settled deepest hook had a median value of 60 m for 333 swordfish sets. Tuna longline gear deployed more hooks between floats (mean = 26.8), and the observed median depth of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
138
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(150 citation statements)
references
References 11 publications
9
138
1
2
Order By: Relevance
“…However, a greater variation of this time (3-15 hours), certainly related to the time taken by the search for albacores, is motivated by the growing trade in fresh tuna. BIGELOW et al (2006) in a study conducted in Hawaii also showed that the soak time is increased when the vessels attempt to capture swordfish (between 11 and 28 hours), and albacores (between 13 and 31 hours). A study of the longline fleet based on São Paulo state, found a mean soak time of 20 hours (MOURATO et al, 2011), which is much higher than that recorded in this study.…”
Section: Discussionmentioning
confidence: 92%
“…However, a greater variation of this time (3-15 hours), certainly related to the time taken by the search for albacores, is motivated by the growing trade in fresh tuna. BIGELOW et al (2006) in a study conducted in Hawaii also showed that the soak time is increased when the vessels attempt to capture swordfish (between 11 and 28 hours), and albacores (between 13 and 31 hours). A study of the longline fleet based on São Paulo state, found a mean soak time of 20 hours (MOURATO et al, 2011), which is much higher than that recorded in this study.…”
Section: Discussionmentioning
confidence: 92%
“…where k is the sagging ratio defined as the length of horizontal line divided by the length of mainline between unit baskets and estimated as the ratio of the speed of the mainline thrower to speed of vessel (Bigelow et al 2006). In this study, speed of the line thrower and speed of vessel varied slightly during the trip.…”
Section: Depth Calculationmentioning
confidence: 99%
“…The depth at which fish are captured can provide critical information for understanding the impacts of longline fisheries on targeted and bycatch species (Bigelow et al 2006). Deploying longline hooks at appropriate depths can greatly improve catch of desired species, such as bigeye tuna (Thunnus obesus; Suzuki et al 1977, Boggs 1992) and billfishes (Boggs 1992), and reduce bycatch of protected species and untargeted species, such as sea turtles (Gilman et al 2006, Beverly et al 2009).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations